Comparison of Water Balance and the Needs of Selected Agricultural Crops for Water in Pomurje Region - Kikec, Tatjana (Journal for Geography, 2016)
In this article we investigate the state of the water balance in the Pomurje region, its quantitative, temporal and spatial perspectives, and compare it with the needs of selected agricultural crops for water in various stages of development. The comparison has shown that the distribution status of the water balance throughout the year – in Pomurje region it is negative between April and the second half of August – is quite favourable for winter grain. The grain lacks water only in the second half of the growing season, as it is picked before the greatest shortage of water in the soil during the summer months. Most other agricultural crops such as corn, potatoes, sugar beet, pumpkins and vegetables face water scarcity in the ground for the major part of the growth period. Their most sensitive stages of development take place during summer months when the water deficit in the soil is the largest, thus they are greatly affected. The consequences are damaged crops and lower quantities of crops with inferior quality.
Keywords: water balance; Pomurje region; agricultural crops; potential evapotranspiration of plants